Application of Livestock Waste Liquid Fertilizer and Mychorriza Biofertilizer on The Growth of Biduri (Calotropis gigantea) - Muhammad Naufal Adani; Samanhudi Samanhudi; Amalia Tetrani Sakya; Sri Hartati; Muji Rahayu; Anne Sukmawati (Journal of Biodiversity and Biotechnology, 2022)
Biduri (Calotropis gigantea) was a plant with several benefits, namely as a medicinal plant and textile material. Biduri was a wild plant that could grow in various types of soil conditions. The existence of biduri was still not fully utilized by many people. So it was necessary to develop the cultivation technology of Biduri to take advantage of this plant. This research was conducted at the field laboratory of Jumantono, Faculty of Agriculture, Universitas Sebelas Maret, Karanganyar, and used a factorial Randomized Complete Block Design (RCBD), which consisted of 2 factors, namely organic liquid fertilizer from livestock waste and mycorrhizae. Livestock waste liquid fertilizer consists of 40ml/kg soil cow urine, 40ml/kg soil goat urine, 40ml/kg soil rabbit urine, and 40ml/kg soil fish waste. Mycorrhizae consisted of 0 grams/plant, 5 grams/plant, 10gram/plant, and 15gram/plant. There were 20 treatment combinations repeated 3 times, so the total was 60 treatment combinations. The interaction between livestock waste liquid fertilizer and mycorrhizae did not significantly affect all the physiological observation variables. The results showed that the application of livestock waste liquid fertilizer had no significant effect on all observations of physiological variables. Giving mycorrhizae shows that it can increase the number of stomata and the width of stomata aperture.